2021
DOI: 10.1038/s41419-021-03534-w
|View full text |Cite
|
Sign up to set email alerts
|

Small intestinal immune-environmental changes induced by oral tolerance inhibit experimental atopic dermatitis

Abstract: Atopic dermatitis is a chronic skin inflammatory disease mediated by Th2-type immune responses. Although intestinal immune responses have been shown to play a critical role in the development or prevention of atopic dermatitis, the precise influence of intestinal immunity on atopic dermatitis is incompletely understood. We show here that orally tolerized mice are protected from experimental atopic dermatitis induced by sensitization and epicutaneous (EC) challenge to ovalbumin. Although the expression of Th2-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…A study from Gachon University developed a murine model of AD by the repeated epicutaneous exposure of tape-stripped skin to ovalbumin. It revealed that the induction of oral tolerance protects mice from AD-like dermatitis and inhibits the increase in small intestinal eosinophils and dysregulated alterations in the gut microbiome ( Um et al, 2021 ). Combining previous studies of AD mice, it may suggest that gut bacterial strains can provide stimulation and promote maturation of the infant immune system.…”
Section: Gut Microbiome and Inflammatory Skin Diseasesmentioning
confidence: 99%
“…A study from Gachon University developed a murine model of AD by the repeated epicutaneous exposure of tape-stripped skin to ovalbumin. It revealed that the induction of oral tolerance protects mice from AD-like dermatitis and inhibits the increase in small intestinal eosinophils and dysregulated alterations in the gut microbiome ( Um et al, 2021 ). Combining previous studies of AD mice, it may suggest that gut bacterial strains can provide stimulation and promote maturation of the infant immune system.…”
Section: Gut Microbiome and Inflammatory Skin Diseasesmentioning
confidence: 99%
“…Genomic DNA was extracted from frozen stool samples using the QIAamp Fast DNA Stool Kit (QIAGEN, Hilden, Germany) according to the manufacturer’s instructions. Amplification and sequencing of the 16S rRNA gene were performed as previously described 21 .…”
Section: Methodsmentioning
confidence: 99%
“…By secreting cytokines eosinophils can switch the immune response. So, when activated, they are able to secrete both Th1 cytokines (IFN-γ, IL-8) and Th2 cytokines (IL-4, IL-13) [ 155 ], and also participate in the immunotolerance reaction by secreting IL-10, TGF-β [ 156 , 157 ].…”
Section: The Immune System and Environmental Survivalmentioning
confidence: 99%